Characterization of microbial protein obtained from agro-industrial waste - Chafla Moina, Ana Lucia (2015)
Microbial protein was characterized in the Biotechnology laboratory of the Polytechnic School of Chimborazo (Escuela Superior Politécnica de Chimborazo). This was obtained from a mixture of whey, passion fruit peel (Passiflora edulis), and ripe banana (Musa paradisiaca), using solid state fermentation (SSF). Treatments were allocated under a completely randomized design, with a 4x4 factorial arrangement and three repetitions. Factors were: whey (0, 5, 10 and 15 %) and fermentation time (FT) (0, 12, 24, and 36 h). Food indicators, pH, ammonia-nitrogen (NH3), volatile fatty acids (VFA), and yeast count were assessed. The pH increased as whey was added, between 4.9 and 5.6, however, regarding fermentation time, the value differs significantly across treatments (P≤  0.001). The  number  of  yeast  cells  increased  significantly  (P<  0.001)  in treatments with 10 and 15 % whey with respect to the control. There was a significant relation (P<0.001) between VFA production and FT. The treatment with the highest VFA production was the one with 15% whey at 24 h with 13.33 meq/L. Crude fiber (CF) decreased (P ≤0.0001) with the increasing levels of whey. True protein (TP) increased (P ≤ 0.0001) as whey and FT levels increased in each treatment. Adding up to 15% of whey on the passion fruit peel and ripe banana enabled the obtaining of better food and fermentation indicators during microbial protein production.